Human rights and the food sovereignty movement : reclaiming control - Claeys, Priscilla (London ; New York : Routledge, 2015)
"The book assesses efforts to achieve the international recognition of new human rights for peasants at the international level, namely the 'right to food sovereignty' and 'peasants' rights'. It explores why La Via Campesina was successful in mobilizing a human rights discourse in its struggle against neoliberalism, and also the limitations and potential pitfalls of using the human rights framework"--
1. Introduction -- 2. The right to food sovereignty -- 3. The rights of peasants -- 4. The right to food -- 5. The challenges of using rights -- 6. Transforming the right to food.
Includes bibliographical references and index.
Keywords: Food supply; Right to food; BUSINESS & ECONOMICS -- Infrastructure; Social Science -- General; Food supply; Right to food